Adipose-derived stem cells decrease pain in a rat model of oxaliplatin-induced neuropathy: Role of VEGF-A modulation. (15th March 2018) - Di Cesare Mannelli, Lorenzo; Tenci, Barbara; Micheli, Laura; Vona, Alessia; Corti, Francesca; Zanardelli, Matteo; Lapucci, Andrea; Clemente, Ann Maria; Failli, Paola; Ghelardini, Carla
Abstract: Oxaliplatin therapy of colorectal cancer induces a dose-dependent neuropathic syndrome in 50% of patients. Pharmacological treatments may offer limited relief; scientific efforts are needed for new therapeutic approaches. Therefore we evaluated in a preclinical setting the pain relieving properties of mesenchymal stem cells and its secretome. Rat adipose stem cells (rASCs) were administered in a rat model of oxaliplatin-induced neuropathy. A single intravenous injection of rASCs reduced oxaliplatin-dependent mechanical hypersensitivity to noxious and non-noxious stimuli taking effect 1 h after administration, peaking 6 h thereafter and lasting 5 days. Cell-conditioned medium was ineffective. Repeated rASCs injections every 5 days relieved pain each time with a comparable effect. Labeled rASCs were detected in the bloodstream 1 and 3 h after administration and found in the liver 24 h thereafter. In oxaliplatin-treated rats, the plasma concentration of vascular endothelial growth factor (pan VEGF-A) was increased while the isoform VEGF165 b was upregulated in the spinal cord. Both alterations were reverted by rASCs. The anti-VEGF-A monoclonal antibody bevacizumab (intraperitoneally) reduced oxaliplatin-dependent pain. Studying the peripheral and central role of VEGF165 b in pain, we determined that the intraplantar and intrathecal injection of the growth factor induced a pro-algesic effect. In the oxaliplatin neuropathy model, the intrathecal infusion of bevacizumab, anti-rat VEGF165 b antibody and rASCs reduced pain. Adult adipose mesenchymal stem cells could represent a novel approach in the treatment of neuropathic pain. The regulation of VEGF-A is suggested as an effective mechanism in the complex response orchestrated by stem cells against neuropathy. Graphical abstract: Highlights: Adipose stem cells relieve neuropathic pain induced by chemotherapy. The pain killer effect has a rapid onset and lasts until 5 days. High levels of VEGF are related to oxaliplatin-dependent neuropathic pain. The pain relieving effects of stem cells are related to a decrease of VEGF levels.